Understanding crime trends in a hybrid society: the digital drift - Aebi, Marcelo F.; Miró Llinares, Fernando; Caneppele, Stefano (SpringerBriefs in criminology, 2025)
Chapter 1 The Roots and Ramifications of Criminology's Progressive Ethos: Navigating Theory, Practice, and Politics -- Chapter 2 A narrative review of the debate on the so-called international crime drop -- Chapter 3 Digitalization, social change and crime trends: a literature review to build a conjecture -- Chapter 4 Crime Opportunities, Lockdowns, and online video Games: the digital leisure hypothesis (and more on the impact of digitalisation on crime trends) -- Chapter 5 Observing, Measuring, and Researching Cybercrime: A scoping review of systematic reviews since 2000.